Utilization of Nostoc piscinale as Potential Biofertilizer to the Growth and Development of Oryza sativa L. - Rebecca Go Oco; Mark Kevin Devanadera; Ruel Valerio Robles de Grano (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Nostoc is a blue-green cyanobacteria that produce their food through photosynthesis and nitrogen fixation. These organisms undergo nitrogen fixation and provide a potential nitrogen source for growth and development. Since rice is known as one of the world’s staple foods, especially in Asia, this study aims to determine the utilization of Nostoc piscinale as a potential biofertilizer for planting rice crops. N. piscinale was inoculated into three subcultures and incubated for 87 to 170 days, and then analyzed for nitrogen-fixing activity and rice plant development. Growth of cyanobacteria showed a significant increase in chlorophyll a starting from day 30 up to day 170 while nitrogen-fixing activity remained constant from day 4. On the other hand, the growth and development of rice treated with cyanobacteria showed correlated trends with commercial fertilizer (CSF) in terms of root and shoot (growth and fresh weight) and chlorophyll a content with no statistical differences (p-value ≥ 0.05). Nitrogen tests indicate the utilization of ammonia produced by N. piscinale and the change in soil pH. After harvesting the samples at 20 days and measuring the soil pH, the cyanobacterial samples were seen to lower the soil pH before planting, which is significantly different from the untreated and CSF-treated samples. The utilization of nitrogen for the growth and development of Oryza sativa subsp. indica proved that N. piscinale would be a positive alternative source of nitrogen due to the results obtained from the soil nitrogen composition and soil pH.